Thermophysical Properties of Pressed and Casted Carbon‐Bonded Alumina (Al2O3‐C) up to 800 °C1. Issue 12 (31st October 2013) - Goetze, Pitt; Wulf, Rhena; Gross, Ulrich; Dopita, Milan; Rafaja, David; Dudczig, Steffen; Aneziris, Christos G.; Klemm, Yvonne; Biermann, Horst B.; Aneziris, Christos G.
<x xml:space="preserve">Abstract</x> Carbon‐bonded alumina manufactured by use of a novel binding system Carbores® P are among the most promising materials for future high temperature industry products. Their secure application is based on an accurate knowledge of their thermophysical properties. In this work, an experimental investigation will be presented for the determination of the coefficient of thermal expansion, thermal diffusivity, specific heat, and thermal conductivity within a temperature range up to 800 °C. Experiments are represented for materials containing various mass fractions of Carbores® P, produced through various processes. It is found that the coefficient of thermal expansion and thermal conductivity are decreased by an increasing mass fraction of Carbores® P, while the specific heat is not affected.